Static secondary ion mass spectrometry investigation of corrosion inhibitor Irgamet®39 on copper surfaces treated in power transformer insulating oil. (September 2015) - Facciotti, Marco; Amaro, Pedro S.; Brown, Richard C.D.; Lewin, Paul L.; Pilgrim, James A.; Wilson, Gordon; Jarman, Paul N.; Fletcher, Ian W.
Graphical abstract: Highlights: SSIMS was used to study corrosion inhibition of copper treated in insulating oil. Desorption experiments allowed the study of the inhibitor stability in vacuum. The energy of desorption of tolyltriazole under SSIMS conditions was calculated. SSIMS imaging was shown to be an applicable new diagnostic tool for transformers. Abstract: Static secondary ion mass spectrometry was used to study the corrosion inhibitor Irgamet ® 39 on the surface of copper treated in insulating oils and the effect of temperature changes, by means of temperature programmed desorption experiments under vacuum, on metal coverage. Four commercial oils, both corrosive and non-corrosive, showed no significant influence on the stability of the tolyltriazole layer and the energy of its main desorption event from copper was calculated around 100 kJ mol −1 . Finally, an example of ion imaging as diagnostic tool to track the distribution of corrosion inhibitor and by-products in decommissioned or failed power transformers is described.